A self-regulating braking mechanism in black-hole X-ray binaries - Meyer, F; Meyer-Hofmeister, E (2001)
The outbursts of black hole X-ray transients can be understood as caused by a limit cycle instability in the accretion disk, similar to dwarf nova outbursts. For adequately low mass overflow rates from the companion star long outburst recurrence times are expected. But the fact that we find predominantly long recurrence times or that only one X-ray nova outburst was detected at all poses a problem. The question arises whether any braking mechanism could act in a way that long recurrence times are favoured.We suggest that a circumbinary disk exists and brakes the orbital motion of the binary stars by tidal interaction. The irradiation during an outburst leads to mass loss by winds from the circumbinary disk, relieving the braking force until the removed matter is refilled by diffusion from outer parts. We show that this reduction of braking will self-adjust the mass transfer to the marginal rate that gives long recurrence times.